PENINGKATAN PRESTASI BELAJAR MELALUI APLIKASI CANVA SELAMA PEMBELAJARAN DARING MASA PANDEMI COVID-19 - Maryunani Maryunani; Nur Hasan (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the implementation of online learning at SDN Krembangan Selatan III during the COVID-19 pandemic, to measure the ability of teachers to design and implement creative and innovative online learning according to student conditions during School from Home (SFH). In addition, this research was conducted to see the learning achievement of class VI students when participating in online learning. Teachers carry out digital-based learning using the Canva for education application in delivering learning materials to students. The features used in the delivery of the material is presentation. The presentation features display in the form of power points which can be recorded by showing the faces of the presenters (educators) in delivering material to students. Using descriptive qualitative research with the main focus of improving student learning outcomes. The results showed that the creativity of online learning has achieved the expected goals, especially after students used the Canva application, it becomes more innovative, and interested in participating in online learning. It also has impact on student academic achievement. The average value showed in the pre-test of 65.4 and post-test of 82.2. This showed that the student's academic results while using Canva are in a very good category. The use of the Canva application also affects the percentage who passed the grade, from 20% to 90%. Based on the results, it can be concluded that Canva for education can be an innovative digital learning media and can improve the learning achievement of sixth grade students at SDN Krembangan Selatan III Surabaya.